Analysis of Carrying Capacity of Crop Agricultural Land in Banten Province - Tristan, Abraham Cardenas (EDP Sciences, 2023)
One of the problems with the need for land is the decreasing amount of agricultural land in Banten Province in 2020 which also affects the inability to meet the food needs of the population independently. This study aims to determine the level of carrying capacity of paddy agricultural land in meeting the food needs of the people in Banten Province. Spatially, this research covers 4 regencies and 4 cities in Banten Province, namely Pandeglang Regency, Lebak Regency, Tangerang Regency, Serang Regency, Tangerang City, Cilegon City, Serang City, and South Tangerang City. The data used is secondary data taken from the Central Statistics Agency and the Agriculture Office of Banten Province. The calculation of Carrying Capacity of Agricultural Land in this study used a combination of theories from Odum, Christeller, Ebenezer Howard, and Isard. The variables used in the calculation included the harvested land area (Ha), population size, average rice production per hectare (Kg/Ha), and the Minimum Physical Requirement with a predetermined value of 265. Data processing was carried out using Microsoft Office Excel and map making was carried out using ArcGIS software. The results showed that There are 2 districts with class II and there are 6 regencies/cities classified into the carrying capacity of class III. © 2023 EDP Sciences. All rights reserved.